Let’s remember all by name (to the 60th anniversary of Great Victory is devoted) - S. G. Ronzhin; I. S. Ronzhin (Бюллетень сибирской медицины, 2005)
There is presented some biographical data about war leaders of medical department of Tomsk State University, head of war department of Tomsk medical Institute that were participants of Great Patriotic War. Military doctors contributed greatly in survivability of Red Army-Winner. They made a great contribution in order to win a victory over the enemy. Our heart should remember their names. These are names of people that gave us possibility to consider ourselves the heirs of Great Victory.